Philosophy of Education: A Brief Analysis from Modernist and Post-Modernist Perspective - Samuel Aloysius Ekanem (dialektika kontemporer, 2021)
For a very long period, the philosophy of education has been an important area of study. It is important because it explains how educational theories evolve. An understanding of philosophy is therefore essential in guiding and critiquing the development of educational theory. The purposes of education are articulated and expressed at a practical level through the curriculum. Philosophy sets the ground for the development of education. The inherent and interpretative meaning of education can be realized only through philosophy. Another important aspect of this relationship is the impact of various philosophical epochs in the field of education, like pre-modernism and post-modernism, on education. Both modernism and postmodernism have brought drastic revolutions in the fields of philosophy in general and philosophy of education in particular. The rapid changes in the social and economic spheres were thus paralleled by equally dramatic changes in the world of theory and ideas. The essence of this paper is to trace a brief analysis of the philosophy of education from the modern to the post-modernist strand.